Asian life imprisonment in worldwide perspective - Zyl Smit, Dirk van (Life Imprisonment in Asia, 2023)
This chapter conducts a preliminary overview of the current state of knowledge about life imprisonment in Asia, as developed in this book, and compares it with what is known about life imprisonment internationally. The chapter explains the important role that debates about the future of the death penalty have played in understanding policies towards life imprisonment in Asia in particular. It shows how the complexity of life imprisonment has been reflected in the way it is defined in Asian countries. These definitions are largely a product of the colonial history of the countries concerned. The chapter also summarises what is now known about the process of imposing and enforcing life imprisonment across Asia, and the extent to which this knowledge is supported by statistics, as well as by evidence of how life-sentenced prisoners are treated in practice. Finally, the chapter considers the use that is made of international human rights standards in critiquing the life imprisonment regimes in many Asian countries. It concludes that, while there is a lively policy debate about life imprisonment in Asia, knowledge of what is happening on the ground is sometimes wanting. This book is a significant first step in addressing that knowledge gap.